Literature Review: Infant formulas with human milk oligosaccharides on gut microbiome and intestinal immune system - Carissa Wira Amadea; A’immatul Fauziyah (Poltekkes Kemenkes Aceh, 2023)
Background: Infant formula has a similar composition to breast milk, especially on key components like proteins, fats, and functional oligosaccharides. However, significant differences exist between bovine milk-based formula and human breast milk, particularly in the abundance and diversity of human milk oligosaccharides (HMOs). HMOs are pivotal in shaping the infant gut microbiome and immune system, with potential implications for infant health and development.Objectives: The literature review aimed to explore the role of HMOs in shaping the gut microbiome and strengthening the intestinal immune system in infants.Methods: Descriptive research was carried out in May-August 2023 using the literature review method. The design and implementation of this study referred to the guidelines outlined in the Preferred Reporting Items for Systematic Reviews and Meta-Analysis (PRISMA) for Randomized Controlled Trials (RCTs). Literature sources were obtained from PubMed, Elsevier, Medline, Nature, PLOS, MPDI, JAMA, and Scopus publication databases with a limitation of the last ten years (2013-2023). One hundred twenty articles were obtained with these keywords and then selected in stages according to predetermined criteria. Six articles that met the criteria were retrieved from 2013-2023. The articles obtained were compiled, analyzed, and concluded by looking for similarities and dissimilarities, giving views, comparing, and summarizing.Results: The review revealed that HMOs significantly influenced the composition and function of the infant's intestinal microbiota, inhibiting harmful pathogens in the intestine. Therefore, HMOs as prebiotics were crucial in promoting intestinal immune system health in infants.Conclusion: Human Milk Oligosaccharides (HMOs) in infant formula substantially impacted the gut microbiome composition and the infant's intestinal immune system. Studies consistently showed that HMOs influenced the growth and diversity of gut bacteria, leading to outcomes similar to those seen in breastfed infants.